ASSISTANCE IN RENEWAL PT GOLDWELL PLASTIC INDONESIA’S TEMPORARY EMPLOYMENT CONTRACT IN ACCORDANCE WITH THE APPLICABLE LAWS - Desy Crisyanti; Lu Sudirman (ConCEPt - Conference on Community Engagement Project, 2022)
Employment contract is the binding connection between companies and its workers. Employment contract itself can be divided into two types which are the temporary employment contract and the permanent employment contract. Temporary employment contract often found in larger companies such as PT Goldwell Plastic Indonesia. Temporary employment contract is one of company’s legal document which is very crucial and must be drafted in accordance with provisions of applicable laws and regulations. With the legalization of UU No. 11 Tahun 2020 about Cipta Kerja which includes the revision of UU No. 13 Tahun 2003 about Ketenagakerjaan leads to the re-evaluation of the temporary employment contract that was used in PT Goldwell Plastic Indonesia in order to be accordance with the latest provisions of applicable laws and regulations. In order to achieve that, writer as student of law made an agreement with partner to revised the temporary employment contract in accordance with the latest provisions of applicable laws and regulations.